Image of Power : Portrayals of Russian Militarism and Military Power on the Website Putin. 20 Years - Olkkonen, Milla (My University, 2025)
This thesis deals with the portrayal of militarism and military power by the Presidential Administration of the Russian Federation on the website “Putin. 20 Years”. The website was published in 2019 in celebration of President Vladimir Putin’s twenty years in power and it details the most memorable moments of Russia’s history from 1999 to 2019. For decades now, the Presidential Administration has worked to foster a certain image around President Putin. Throughout the years, this image has morphed together with the image of Russia as a whole. The image the Kremlin has built is largely centered around the aim of projecting power. In the case of Putin’s Russia, the power is specifically hard power, and it has often manifested as use of force. The research material consists of photographs, and therefore this thesis falls into the category of historical image research. Examining Putin’s time in power through photographs is justified as his presidency is exceptionally visual. Image research attempts to approach the worldview of the picture producers, in this case focusing on militarism and military power. The research question is: what subjects under the larger themes of militarism and military power appear in the material? In the case of this thesis militarism covers cultural aspects, while military power focuses more on the ways the administration advertises its abilities. The two main ways militarism and military power manifest on the website are ‘remembrance’ and ‘show of power’. Remembrance refers to portrayals of Russian military history, veterans, and different celebrations. Remembrance has a distinct sense glorifying sacrifice and suffering, suggesting that this angle is key to how the Presidential Administration wants to frame history. Show of power draws the focus on to the future and the military potential that Russia has, by flaunting the country’s military industry as well as potential for battle. Show of power also tries to justify use of force by showing that Russia is and has been under attack.

Tämä pro gradu käsittelee militarismin ja sotilaallisen voiman esittämistä Venäjän presidentinhallinnon vuonna 2019 julkaisemalla sivustolla ”Putin. 20 Years”. Sivusto tehtiin juhlistamaan presidentti Vladimir Putinin kaksikymmenvuotista taivalta Venäjän johdossa ja se esittelee Venäjän lähihistorian merkittäviä hetkiä vuosilta 1999–2019. Venäjän presidentinhallinto on nyt jo vuosikymmenten ajan pyrkinyt luomaan ja ylläpitämään tietynlaista julkisuuskuvaa presidentti Putinista. Vuosien aikana tämä kuva on yhdistynyt Venäjän itsensä julkisuuskuvan kanssa. Kremlin luoma kuva on perustunut laajalti pyrkimykseen projisoida voimaa. Putinin Venäjän tapauksessa tämä voima on spesifisti kovaa voimaa ja se on useissa tapauksissa ilmennyt voimankäyttönä. Tutkimusmateriaali koostuu valokuvista, näin ollen tämä pro gradu on historiallista kuvatutkimusta. Putinin valtakauden tutkiminen valokuvien kautta on perusteltua, sillä hänen presidenttiytensä on poikkeuksellisen visuaalista. Kuvatutkimuksen keinoin pyritään lähestymään kuvien tuottajien maailmankuvaa, tässä tapauksessa keskittyen militarismin ja sotilaallisen voiman teemoihin. Tutkimuskysymys on: mitkä aiheet militarismin ja sotilaallisen voiman sisällä nousevat esiin materiaalissa? Tämän tutkielman puitteissa militarismilla viitataan sen kulttuurisiin ilmentymiin sotilaallisen voiman viitatessa tapoihin, joilla hallinto esittelee omaa kyvykkyyttään. Militarismi ja sotilaallinen voima esiintyvät sivustolla erityisesti ”muistamisen” ja ”voimannäytön” kautta. Muistaminen viittaa Venäjän sotahistorian, veteraanien ja erilaisten juhlien esittämiseen. Muistamiseen liittyy vahvasti uhrauksen ja kärsimyksen glorifiointi, mikä viitannee siihen, että tämä on oleellista tavalle, jolla presidentinhallinto haluaa esittää historiaa. Voimannäyttö keskittyy enemmän tulevaisuuteen ja Venäjän sotilaalliseen potentiaaliin esittelemällä Venäjän sotateollisuutta sekä kykyä käydä sotaa. Voimannäyttö pyrkii myös oikeuttamaan voimankäytön näyttämällä, että Venäjä on ollut ja on edelleen itse hyökkäyksen kohteena.
Keywords: Militarism, Military power, Russian Federation, Putin, Presidential Administration, Great Patriotic War, Public diplomacy, Historical image research, militarismi, sotilaallinen voima, Venäjän federaatio, Putin, presidentinhallinto